Clinical Study on Treatment of Acute Lower Extremity Arterial Embolism With Straub Thrombus Removal System - Zhao, Liang; Cai, Hui; Song, Qiang (Frontiers in Surgery, 2022)
Background. Acute lower extremity arterial embolism (ALEAE) is a common and frequently-occurring disease in clinic. Although thrombectomy with arteriotomy has been widely used and developed in clinic, there is a high probability of embolic recurrence after operation. The present study investigated the clinical efficacy of the Straub Rotarex system in the treatment of ALEAE, as it was capable of removing exfoliative substances in acute and chronic cavities and exposing diseased vessels. Materials and Methods. We accessed our institutional database and retrospectively screened all patients with ALEAEs who received surgical treatment between April 2018 and April 2021. To observe the clinical efficacy, surgical indicators, incidence of postoperative complications and recurrence rate of treatment with Straub Rotarex system and arteriotomy thrombectomy, and analyze the risk factors for recurrence of embolism after treatment with Straub Rotarex system by multivariate Logistic regression model. Results. The total effective rates of the observation group and the control group after operation were 100% and 93.75% respectively, and there was no significant difference between the two groups (P > 0.05). The intraoperative blood loss , postoperative off-bed time and hospital stay time in the observation group were significantly lower than those in the control group, and the operation time and hospitalization expenses were significantly higher than those in the control group (P < 0.05). The incidence of postoperative complications in the observation group was 3.13%, which was significantly lower than 18.76% of that in the control group (P < 0.05). The recurrence rates of the observation group and the control group were 15.63% and 18.76%, respectively. There was no significant difference in the recurrence rate between the two groups (P > 0.05). Atrial fibrillation was an independent risk factor for recurrence after Straub thrombus removal system (P<0.05). Conclusion. Straub thrombus removal system is an effective method for the treatment of ALEAE. Although it prolongs the operation time and increases the operation cost as compared with thrombectomy, it effectively improves the operation safety, postoperative life quality and postoperative recovery, thus worthy of clinical promotion. Atrial fibrillation is an independent risk factor for recurrent embolism after Straub thrombus removal system.